2001
DOI: 10.1523/jneurosci.21-17-06492.2001
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Dependent Synaptic Plasticity in the Striatal Cholinergic Interneurons

Abstract: The striatum, the input stage of the basal ganglia, is a critical brain structure for the learning of stimulus-response habits as well as motor, perceptual, and cognitive skills. Roles of dopamine (DA) and acetylcholine (ACh) in this form of implicit memory have long been considered essential, but the underlying cellular mechanism is still unclear. By means of patch-clamp recordings from corticostriatal slices of the mouse, we studied whether the identified striatal cholinergic interneurons undergo long-term s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
115
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 51 publications
9
115
2
Order By: Relevance
“…Thus, a D2-selective attenuation of feedforward inhibitory neuron input to cholinergic neurons was observed in WT, but not KO, slices. This is consistent with D2-like presynaptic suppression of cortically-evoked IPSPs reported in rat striatal cholinergic neurons (Pisani et al, 2000;Suzuki et al, 2001;Centonze et al, 2003). …”
supporting
confidence: 90%
See 3 more Smart Citations
“…Thus, a D2-selective attenuation of feedforward inhibitory neuron input to cholinergic neurons was observed in WT, but not KO, slices. This is consistent with D2-like presynaptic suppression of cortically-evoked IPSPs reported in rat striatal cholinergic neurons (Pisani et al, 2000;Suzuki et al, 2001;Centonze et al, 2003). …”
supporting
confidence: 90%
“…Although cortical stimulation did not produce prominent excitation (EPSPs) in WT cholinergic-like neurons, in part due to their depolarized membrane potentials, corticallyevoked disynaptic IPSPs were readily observed, and D2-like receptor stimulation potently attenuated the evoked IPSPs in these neurons. This is consistent with studies in the rat dorsal striatum showing that D2 agonists inhibit local GABA release and reduces spontaneous and evoked disynaptic inhibitory potentials in striatal cholinergic neurons (Suzuki et al, 2001;Centonze et al, 2003) via a D2 presynaptic mechanism (Pisani et al, 2005 Aizman et al, 2000) that could account for the observed D2-mediated attenuation of GABAergic IPSPs in WT cholinergic-like neurons. However, FS interneurons do not express DARPP-32 proteins .…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Local intra-NACore antagonism of mAchRs or nAChRs completely and reversibly blocked the acquisition of RMF reinforcement, indicating (1) that activation of both mAchR and nAChR in the NACore is necessary for the conditioning of the positive reinforcing effect of RMF (i.e., for the animal's learning to associate the drug stimulus with the appropriate operant response) and (2) that the ACh release by cholinergic large aspiny interneurons, the second most prevalent neuron population in the striatum including the NACore (Squire et al, 2003), is instrumental for this learning process. Thus, the general rule that striatal cholinergic interneurons play an eminent role in the formation of stimulus-response associations (i.e., learning) (Aosaki et al, 1994;Calabresi et al, 2000;Suzuki et al, 2001;Kitabatake et al, 2003;Mansvelder et al, 2005) also seems to apply to the NACore, a striatal structure dedicated to processing stimuli of high emotional and motivational valence (Haber et al, 1985;Jongen-Relo et al, 1994). Striatal cholinergic interneurons are known to affect GABAergic medium spiny neurons, which constitute the major (95%) neuron population of the striatum and also serve as the major motivational/locomotor output of the striatum (Haber et al, 1985;Heimer et al, 1991;Zahm and Brog, 1992;Meredith and Chang, 1994;Squire et al, 2003;Voorn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%